Dentists' perceptions and barriers to provide oral care for dependent elderly at home, long-term care institutions or hospitals - Albano Porto Cunha Junior; Mateus Bertolini Fernandes dos Santos; Jarbas Francisco Fernandes Santos; Leonardo Marchini (Universidade Estadual de Campinas, 2018)
Aim: The aim of this study was to assess the perceptions and barriers to providing oral health care for the dependent elderly in unconventional settings as reported by dentists in the State of São Paulo, Brazil. The Brazilian elderly population is rapidly growing, and a larger elderly population implies an increasing number of dependent elderly patients. Therefore, investigating the perceptions and barriers reported by dentists for caring for these patients becomes important. Materials and methods: An online survey was sent by e-mail to dentists of a metropolitan area in the State of São Paulo, Brazil. Results: The response rate was 3.65% (n = 125). Only 14.4% of respondents offered home care to the elderly. Lack of experience or training (60.7%) and the small number of home visits (42.9%), were the main reported barriers to providing care for the dependent elderly. Most of the respondents (82.4%) agreed that the age of the patient did not influence their decision to provide care, and 96.8% agreed that delivering care to the elderly could be a rewarding experience. Conclusion: Few respondents offered care to the elderly and some of the most relevant factors considered in the decision to offer care were, experience and training, personal satisfaction and having gerodontology as a stand-alone course during dental school.